Assessment of migration regularity of phthalates from food packaging materials. Issue 10 (12th September 2020) - Liu, Jing‐Min; Li, Chun‐Yang; Yang, Fei‐er; Zhao, Ning; Lv, Shi‐Wen; Liu, Ji‐Chao; Chen, Li‐Jun; He, Ze; Zhang, Yan; Wang, Shuo
Abstract: Phthalate acid esters (PAEs) are one of the essential plastic additives which may lead to plenty of harmful effects, including reproductive toxicity, teratogenicity, and carcinogenicity. Increasing attention has been paid to the migration of plasticizer. In this article, the disposable plastic lunch boxes were taken as the research object. The result showed that dibutyl phthalate (DBP) and diisobutyl phthalate (DIBP) have been mainly found, whose content was 1.5 mg/kg and 2.4 mg/kg, respectively. The LOD was 2 ng/g, and LOQ was 6.7 ng/g. We further investigated the migration of PAEs into the simulated liquid at different temperature conditions. Then, the linear fitting performing by first‐order kinetic migration model revealed that the lower the polarity of the simulated liquid, the larger the rate constant K 1 and initial release rate V 0 . The higher the temperature, the bigger the K 1 and V 0 . Abstract : This study takes disposable plastic lunch boxes as the research object, and determines the types and contents of PAEs, which can provide some data support when considering the safety of lunch boxes. Secondly, polypropylene‐based lunch box was chosen as the migration material. The migration laws of different types of simulants at various temperatures and time points are studied, which lays a foundation for further studying the migration laws of PAEs in food processing and preservation.